Nilai-nilai NILAI-NILAI SOSIAL PROFETIK ISLAM DALAM KODE ETIK KOMISI PEMBERANTASAN KORUPSI REPUBLIK INDONESIA - M. Mualif; Athoillah Islamy (Risalah, Jurnal Pendidikan dan Studi Islam, 2021)
Behind the phenomenon of corruption cases that are still rampant in the Indonesian government, there is an agency that has gained public trust and appreciation, namely the Komisi Pemberantasan Korupsi (KPK). The role and performance of the Corruption Eradication Commission is considered the most successful corruption eradication agency in Indonesia. This study aims to explore and at the same time identify the prophetic social value of Islam in the KPK code of ethics. This qualitative research is in the form of a literature review. This research approach uses a normative-philosophical approach. The primary data source of this research is the code of ethics of the Corruption Eradication Commission (KPK) of the Republic of Indonesia. While the secondary data sources are various scientific researches that are relevant to the main object of the discussion. The analytical theory used is the Ilmu Sosial Profetik paradigm (ISP) which was initiated by Kuntowijoyo. The results of this study conclude the existence of prophetic Islamic social values ​​contained in various values ​​of the KPK code of ethics. First, the value of transcendence (iman) in the code of ethics of religiosity. The existence of the value of religiosity can be said to be a manifestation of the value of Islamic transcendence which makes religious teachings as signs in the activities of social life in the performance of KPK members. Second, the value of humanization in the code of ethics of integrity and professionalism.the values ​​of integrity and professionalism are humanization values ​​that serve as ethical guidelines for KPK members in realizing truth values ​​(amar makruf) in their various duties and activities. Third, the value of liberation (nahi munkar) in the code of ethics for justice and leadership. The KPK code of ethics in the form of justice and leadership values ​​is a fundamental value for KPK members in realizing the orientation of the value of liberation from the political system that has a negative impact on people's lives.